A Gendered Perspective on Local Economic Development: Differences in the Perceived Importance of Public Services in the Business Recruitment Process. Issue 2 (February 2019) - Read, Dustin; Leland, Suzanne Marie
This study uses data from a national survey of economic developers working in local government to explore gender differences in the perceived importance of public services in the business recruitment process. The results of a series of ordinal logistic regression models suggest women are more likely than men to believe public service quality and availability are important concerns for companies considering their region. These findings are consistent with the body of work examining gender gaps in the perceptions of both policymakers and the general public that may have important implications for local governments interested in promoting economic growth.